Penerapan Metode Kooperatif Tipe Bercerita Berpasangan Pada Pelajaran Bahasa Indonesia Kelas IV - Srikandi Octavian (FKIP Universitas Lampung, 2017)
The implementation of cooperative learning type of storytelling in pairs of fourth grade. The purpose of this study was to obtain an objective and complete information about the implementation of the application of cooperative learning type of storytelling in pairs on the subjects of Indonesian in fourth grade SDN 03 Curup the South in an effort to increase the activity of students in the classroom and create a learning fun, so that the learning outcomes can be increased. The method used is descriptive analysis method is a method that does not test the hypothesis but merely describes the information is in accordance with the variables studied, the results of data analysis can be concluded that the implementation of cooperative learning type of storytelling in pairs in learning Indonesian can enhance students’ active learning in the classroom. Keywords: cooperative learning type of storytelling in pairs, Indonesian, activityDOI: http://dx.doi.org/10.23960/jpp.v7.i1.201701